Four and Five Figures of Kifilideen (Power of Base 11) and Antikifilideen (Antipower Of Base 11) Tables - Osanyinpeju, Kifilideen (My University, 2022)
The four figures of power of base numbers tables need to be created for easy synchronization with the existing Logarithm table of power of base 10, which is working on four figures. Although the five figures of power of base numbers tables are more accurate because it is having less approximation in their establishment. The four-figure tables are easy to compute doing utilization because it is having fewer digits to work with. This paper presents the four and five figures of Kifilideen (Power of base 11) and AntiKifilideen (Antipower of base 11) tables for the computation of mathematical problems. The four and five figures are both reliable to work with. However, there is a tradeoff between easy computation (as related to the four-figure table) and more accuracy (as related to the five-figure table) in their utilization.
Keywords: AntiKifilideen Table; Five Figure; Four Figure; FUNAAB; Kifilideen Table; Power of base 11